West African Drumming and Dance in North American Universities: An Ethnomusicological Perspective. George Worlasi Kwasi Dor. 2014. Jackson: University Press of Mississippi. 60 bw photographs, appendices, glossary, bibliography, index, 304 pp. - Kafumbe, Damascus (International Library of African Music, 2014)
pages: 152-154
Keywords: African Music